Cobre, cadmio y plomo en el pez Cyprinodon dearborni, sedimentos y agua en dos lagunas de Venezuela - Toledo, Jesús (2000)
The concentration of copper, cadmium and lead in superficial sediment, water and the fish Cyprinodon dearborni was determined in two coastal lagoons of Sucre State, Venezuela. Chacopata lagoon is hyper saline while Los Patas lagoon is hypo saline and receives significant wastewater from Cumaná city. Water, sediment and fish samples were collected in February 1998. In the laboratory, samples underwent acid digestion and were analyzed by atomic absorption spectophotometry. The mean values of the metals in C dearborni from the Chacopata lagoon were: 159.26 ± 210.68 μg/g for Cu, 44.71 ± 45.58 μg/g for Cd; and 9.31 ± 23.34 μg/g for Pb, while for Los Patos lagoon the mean values were: 64.88 ± 16.30, 19.48 ± 5.81 lUllÍ 22.85 ± 20.00; respectively. In the water column, the metal concentration ranges were; 2.3-11.6, 3.9-5.4 and 21-32 mg/l for copper, cadmium and lead, respectively. These results suggest that metal levels in sediment, water column and organisms in both lagoons do not differ, except for lead, even though only Los Patos receives waste water.